Atividade antibacteriana do isoeugenol frente cepas clínicas de Staphylococcus aureus - Rosa, Lyvia Layanne Silva (2018)
Staphylococcus aureus are microorganisms of great clinical importance, as they are the main agents responsible for bacterial infection, both hospital and community, and are highly resistant to antibiotics. What is resistant to resistance to a challenge for the protection process are the antimicrobial characteristics that are effective in combating these microorganisms. In search of new therapeutic alternatives for the treatment of infections, vegetable products of plant origin can be important sources of new substances that can be used for these flippers, such as essences and their phytochemicals, such as Isoeugenol, a phenylpropanoid. Therefore, the antibacterial activity of isoeugenol against clinical strains of Staphylococcus aureus was evaluated through in vitro assays: Determination of Minimum Inhibitory Concentration (MIC) and Minimum Bacterial Concentration (MBC), determining the efficacy of the concentration on growth kinetics microbial. (time-kill) and association studies of isoeugenol with standard antibiotic (gentamicin). In the evaluation of the antibacterial activity, isoeugenol presented MIC of 512 μg / mL and in the CBM there was growth of the microorganism in all the concentrations. In the assay of death microbial (time-kill), isoeugenol showed bacterial activity that did not depend on the concentration, since the increase of the same did not provoke a significant increase of the activity. The association of phenylpropanoide with gentamicin was promoted for a clinical treatment of S. aureus S.A-116. With this, the results are studied with the use of isoeugenol presents antibacterial activity against S. aureus, either alone or in association with the antimicrobial standard.